2018
DOI: 10.1111/1744-7941.12197
|View full text |Cite
|
Sign up to set email alerts
|

How workplace incivility influences job performance: the role of image outcome expectations

Abstract: This study aimed to investigate whether workplace incivility has negative influences on two types of job performance (i.e. in‐role job performance and innovative job performance), as well as the moderating role of image outcome expectations in the context of healthcare organizations. We tested the research hypotheses using data collected from 727 employees in three Chinese hospitals. The results reveal that workplace incivility has negative influences on both in‐role job performance and innovative job performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 75 publications
0
35
0
5
Order By: Relevance
“…In other words, practice civility and be respectful to everyone in the lab group. Research on workplace incivility makes it clear that an intentional focus on civility and respect is beneficial as it improves interpersonal relationships between participants (see Rule 4; [38]) and productivity [39,40], whereas workplace incivility can result in heightened levels of burnout and withdrawal [41]. This is especially true when the root of that incivility is based on intersecting marginalized identity markers in academia [42,43] (see Rule 9).…”
Section: Rule 5: Be Respectful and Practice Civilitymentioning
confidence: 99%
“…In other words, practice civility and be respectful to everyone in the lab group. Research on workplace incivility makes it clear that an intentional focus on civility and respect is beneficial as it improves interpersonal relationships between participants (see Rule 4; [38]) and productivity [39,40], whereas workplace incivility can result in heightened levels of burnout and withdrawal [41]. This is especially true when the root of that incivility is based on intersecting marginalized identity markers in academia [42,43] (see Rule 9).…”
Section: Rule 5: Be Respectful and Practice Civilitymentioning
confidence: 99%
“…Across industries, employees are exposed to psychological hassles such as incivility (Hutchinson et al, 2018). Specifically, in nursing, incivility is a widespread problem that has garnered much attention in recent years (Laschinger et al, 2013;Jiang et al, 2018). Emerging evidence suggests that incivility has significant implications for nurses, patients and healthcare organizations as a whole (Clark and Springer, 2007).…”
Section: Workplace Incivility and Its Impact On Nurses 301mentioning
confidence: 99%
“…A global study conducted by Pearson and Porath (2009) revealed that the estimated cost expense of workplace incivility on an average for companies was $14,000 per employee because of lost productivity and work time. In fact, recent work on intraprofessional incivility revealed that both employees' in-role job performance and innovative job performance can be negatively influenced by workplace incivility (Jiang et al, 2018). Furthermore, the empirical findings of recent studies on workplace incivility uncovered some acute organizational phenomena in particular "instigated incivility" and "organizational cynicism" (Loh and Loi, 2018;Manzoor et al, 2020;Ozler and Atalay, 2011) being practiced within various professional realms resulting in heightened levels of job burnout and withdrawal or turnover intensions (Loh and Loi, 2018;Manzoor et al, 2020;Tricahyadinata et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on workplace incivility has revealed the outcome of these deviant workplace behavioral actions, such as workplace stress and psychological distress (Cortina et al, 2001;Lim and Cortina, 2005;Anjum et al, 2019, job withdrawal (Pearson et al, 2001Manzoor et al, 2020), lower job satisfaction (Penney and Spector, 2005), lower coworker and supervisor satisfaction (Martin and Hine, 2005;Loh and Loi, 2018), reduced creativity and performance at work (Wilson and Holmvall, 2013;Jiang et al, 2018), higher turnover, depression and work-family conflicts (Lim and Lee, 2011). Further studies have also considered the role of individual differences and the occurrence of incivility (Bunk and Magley, 2011).…”
Section: Introductionmentioning
confidence: 99%